Forest and Nature Governance A Practice Based Approach - Arts, Bas.; Behagel, Jelle; van Bommel, Séverine; de Koning, Jessica; Turnhout, Esther; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
Problems such as deforestation, biodiversity loss and illegal logging have provoked various policy responses that are often referred to as forest and nature governance. In its broadest interpretation, governance is about the many ways in which public and private actors from the state, market and/or civil society govern public issues at multiple scales. Examples range from the United Nations’ Convention on Biological Diversity to national forest programmes. In studies of forest and nature governance the dominant approaches are rational choice and neo-institutionalism. This book takes another perspective. Departing from ‘practice theory’, and building upon scholars like Giddens, Bourdieu, Reckwitz, Schatzki and Callon, it seeks to move beyond established understandings of institutions, actors, and knowledge. In so doing, the book not only presents an innovative conceptual and methodological framework for a practice based approach, but also rich case studies and ethnographies. Examples are participatory forest management in the tropics, REDD policy at global level, European water policy, forest certification and the construction of global biodiversity databases. Taking social practices as the key unit of analysis, this book describes how different practitioners, ranging from local forest managers on the ground to policy makers at the global level, work with trees, forests, biodiversity, wildlife, and so on, and act upon forest policies, environmental discourses, codes of conduct, or scientific insights. It is also about how communities, NGOs, stakeholders, and citizens get involved in forest and nature governance.
Preface -- Introduction -- 1. Prelude to practice: Introducing a practice based approach to forest and nature governance -- 2. From practical science to a practice based approach: A short history of forest policy studies -- Rethinking institutions -- 3. Bricolage practices in local forestry -- 4. What institutions do: Grasping participatory practices in the Water Framework Directive -- 5. Invited spaces and informal practices in participatory community forest management in India -- The global-local nexus -- 6. Global forest governance: Multiple practices of policy performance -- 7. The practice of interaction management: enhancing synergies among multilateral REDD+ institutions -- 8. How do forest markets work? Exploring a practice perspective -- Representing nature? 9. Globalising biodiversity: Scientific practices of scaling and databasing -- 10. Where management practices and experiential practices meet: Public support and conflict in ecosystem management -- 11. Creating scientific narratives: experiences in constructing and interweaving empirical and theoretical plots -- Conclusion -- 12. The promise of practice: The value of the practice-based approach for forest and nature governance studies.
Keywords: Forestry; Environmental law; Environmental policy; Nature conservation; Political science; Social sciences; Biodiversity; Forestry; Environmental Law/Policy/Ecojustice.; Nature Conservation; Political Science; Social Sciences, general; Biodiversity